In-person and cyber dating abuse: A longitudinal investigation. (December 2021) - Lu, Yu; Van Ouytsel, Joris; Temple, Jeff R.
While studies have identified associations between cyber and in-person dating abuse, most research has relied on cross-sectional data, limiting the ability to determine temporality. This study tested the longitudinal associations between cyber and physical and psychological forms of in-person dating abuse. Data were from an ongoing longitudinal study following a group of high school students originally recruited in Southeast Texas, US, into their young adulthood. Three waves of data (Waves 4–6) were used, with each wave collected one year apart. At Wave 4, participants' age ranged from 16 years to 20 years (mean = 18.1, median = 18.0, SD = .78). The analytical sample consisted of 879 adolescents/young adults (59% female, 41% male; 32% Hispanics, 28% Black, 29% White, and 11% other) who completed the dating abuse questions. Cross-lagged panel analysis showed that dating abuse victimization and perpetration were predictive of subsequent dating abuse of the same type. Cyber dating abuse perpetration was found to predict subsequent physical dating abuse perpetration as well as physical dating abuse victimization, but not vice versa. Further, cyber dating abuse perpetration predicted psychological dating abuse victimization, but not vice versa. Cyber dating abuse victimization was not significantly associated with either physical or psychological dating abuse temporally. Overall, findings suggest that cyber dating abuse perpetration may be a risk marker for both physical and psychological forms of in-person dating abuse. Interventions may benefit from targeting cyber dating abuse perpetration as means to prevent in-person dating abuse.